2021
DOI: 10.1021/acsnano.1c06675
|View full text |Cite
|
Sign up to set email alerts
|

Edge-Hydrogenated Germanene by Electrochemical Decalcification-Exfoliation of CaGe2: Germanene-Enabled Vapor Sensor

Abstract: Two-dimensional germanene has been recently explored for applications in sensing, catalysis, and energy storage. The potential of this van der Waals material lies in its optoelectronic and chemical properties. However, pure free-standing germanene cannot be found in nature, and the synthesis methods are hindering the potentially fascinating properties of germanene. Herein, we report a single-step synthesis of few-layer germanene by electrochemical exfoliation in a nonaqueous environment. As a result of simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 82 publications
4
20
0
Order By: Relevance
“…The structure of the exfoliated siligene and its intrinsic crystal CaSiGe were analysed by XRD (Figure 6a). The XRD pattern possesses relative similarity to hexagonal R3̅ m symmetry when compared with the CaSi2 and CaGe2, [1,9] and aligns with the SAED patterns (Figure 4b).…”
Section: Synthesis and Characterization Of The Materialssupporting
confidence: 68%
See 2 more Smart Citations
“…The structure of the exfoliated siligene and its intrinsic crystal CaSiGe were analysed by XRD (Figure 6a). The XRD pattern possesses relative similarity to hexagonal R3̅ m symmetry when compared with the CaSi2 and CaGe2, [1,9] and aligns with the SAED patterns (Figure 4b).…”
Section: Synthesis and Characterization Of The Materialssupporting
confidence: 68%
“…[16] This is consistent with the results obtained by Raman, FTIR and XPS as well as our previous study on edge-hydrogenated germanene. [9] Chemical analysis of electrochemically exfoliated SiGe and its bulk precursor CaSiGe was performed by XPS (Figure 7). The elemental composition of samples shown in wide-scan survey spectra (Figure 7a, 7d) demonstrates the presence of Si, Ge, C, O, Ca and Au.…”
Section: Synthesis and Characterization Of The Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…556 The results showed that germanane nanosheets are highly sensitive to volatile organic compounds (VOCs), the biomarker, indicating that germanane nanosheets can be used as molecular devices for detecting liver cirrhosis VOCs (Figure 25E). The most recent work by Kovalska et al 573 demonstrated the edge hydrogenation of germanene by electrochemical decalcification-exfoliation of CaGe 2 , enabling germanene specific sensitivity to organic vapors, showing selectivity to methanol over ethanol as a sensor. This result confirms the potential of Ge-based 2D materials as gas sensors.…”
Section: Electronic Sensorsmentioning
confidence: 99%
“…1,2 By contrast, transition metal dichalcogenide (TMD) materials show outstanding quantum confinement effects and strong light-matter interactions, but limited optical wavelength regimes due to the large bandgap. [3][4][5] Besides, various attempts intend to go beyond the aforementioned limited bandgap towards ultra-broadband photodetection by integrating 2D materials with mixeddimensional materials (0D, 1D, and 3D) or introducing midgap defect states. [6][7][8][9][10][11] But these heterostructures formed by structural engineering cannot change the intrinsic feature of a material for ionizing radiation detection.…”
Section: Introductionmentioning
confidence: 99%